Reducing the Consumption of Sugar-Sweetened Beverages among Children and Adolescents - Marya Yenita Sitohang (Populasi, 2022)
This study focused on the link between sugary beverage intake and health consequences, especially in children and adolescents. Children and adolescents consumed more sugary beverages than the general population, increasing their risk of developing excessive weight gain in the future, which may lead to significant health consequences. While there are few studies about sugary drink consumption among Indonesian children and adolescents, there is a need to control the increasing trend of sugar-sweetened beverage consumption in Indonesia. This study looked into studies from other countries to learn more about the determinants of sugary drink consumption, the challenges of reducing sugary drink consumption, and various policies to reduce sugary drink consumption among children and adolescents. Using a scoping review, this study examined 21 papers that were relevant to the study’s objectives. Several researches have linked excessive sugary drinks to a variety of negative health effects in children and adolescents, including an increase in unhealthy weight gain, the onset of hypertension, an increased risk of cardiovascular disease, and diabetes. Determinants of sugary drinks consumption among children and adolescents were socioeconomic status, physical activities, dietary behaviour, parents, and home environment. This study also discovered several policies in different countries intended to reduce sugary drink consumption, such as taxation, institutional changes, and raising awareness. Findings from this study may guide future research on sugar-sweetened beverage consumption among Indonesian children and adolescents, as well as raise the awareness among stakeholders, such as parents, children and adolescents, health professionals, and policymakers, on the need of preventing excessive sugar-sweetened beverage intake.